Doctrine (Fekh) matters that have been discussed by Imam Alnasser Leddinullah Alhassan bin Ali Nin Dawood Almoayadi (died in 1026) in his justification for some holy verse of Quran from Alfurqan and Al-Zukruf - Fadel, Abduljalil Mahyoub (Journal of Islamic Sciences, 2023)
This research aims to shed the light on Imam Alnasser Leddinullah Alhassan Bin Ali Bin Dawood Almoayadi ( died: 1026) ; exposing his method in discussing his book ( Alahd Alakeed, Tafseer Alquran Almajeed, Amuntaza Min Albyan Wattagreed); as well as the importance of his book and its sources, which is considered one of the most significant sources of Fekh Explainition (Tafseer). The researcher has used the inductive method in indicating Imam Alnasser Leddinullah Alhassan Bin Ali Bin Dawood Almoayadi. He also used the historcal method when exposing the author’s own method and style in the book. One of the most remarkable findings the author reached that Imam Alnasser Leddinullah Alhassan Bin Ali Bin Dawood Almoayadi was a giant doctrine interpreter, wise investigator, had rich knowledge, and highly exalted among his current Fekh interpreting theologians. Asserting that he followed best methods of Tafseer and magnified opinions. The book contains a valuable scholarly subject in the field of Tafseer, Holy Quran Science, Language Science, and Essentials of Fekh.